Controversial issues about the “right” monetary order - Hermann Burgard (Intereconomics, 1980)
The European Monetary System (EMS) has now been in operation for about one year. Dr. Burgard explains the main elements of the system and the problems still awaiting solution.
Keywords: 330; European Monetary System